Syair Tumitu wa Tuhyiyu Dalam Diwan al-Akhthal (Kajian Semiotika Riffaterre) - Saepul Millah (Penaoq: Jurnal Sastra, Budaya dan Pariwisata, 2020)
Literary work does not only mean a word but behind the words contain very deep meaning. This research tries to explore the deepest meaning of one of the poems by al-Akhtal in his Diwan Book entitled "Tumitu wa Tuhyiyu" with Riffaterre's semiotic approach. The method used in this research is descriptive qualitative. The results of this study are in reading heuristics. The first verse, mentioning the beginning that causes death (unconsciousness) is drinking khamar, not only unconscious but also forgetting what has happened. The second line explains the conditions experienced by a group of people who drink khamar, that group of people who are unconscious (dead) for three days means that the effects caused after drinking the khamar have a major impact, so it is mentioned when they are aware that their breath has not returned completely. As the model is the first actualization of the matrix. The first actualization of this matrix is in the form of specific or poetic words or sentences. The specificity and poetry of the model is able to distinguish words or other sentences in the poem. In this case the poem above has a poetic sentence structure, that is, the first is in the sentence as follows فعد بنا إلى مثلها بالأمسand تميت وتحيي بعد مىتThese two models were chosen, because they represent the entire sound of the poetic text contained in eight verses. The eight verses of the poem reflect two points, first, about the actual condition of the drinker, that they were originally good, healthy, normal people like humans in general. Second, it emphasizes that the nature of the drinker shows the true state of being conscious (living), although then he experiences two conditions between turning on (conscious) and deadly (unconscious). The poetry matrix which is then obtained is the "mirage of pleasure".